Analysis of Pine Sap Quality Based on Sieve Variations and its Effect on Economic Value - Khusnul Khotimah; Sri Jumini; Ishaq Abdul Hannan (JURNAL PENDIDIKAN MIPA, 2025)
Pine resin is one of the non-timber forest products (NTFPs) that has high economic value. However, the quality and selling value of pine resin are greatly influenced by the container media used during tapping. This study aims to analyze the effect of filter variations on the innovative tool on the quality of the resin and the resulting economic value. The method used is quantitative descriptive through field experiments and analysis of the sales value of the tapping results using two types of tools, namely traditional tools (coconut shells) and innovative tools with two levels of filters and covers. The experiment was conducted for fifteen days on two groups of pine trees that were tapped in parallel. The results showed that although the volume of resin produced was similar, the selling value of the resin from the innovative tool increased up to three times due to the cleaner quality and minimal contamination, with total income increasing from IDR 72,000 to IDR 216,000 for six trees over fifteen days. The community also responded positively to the practicality, safety, and effectiveness of the tool. This innovation contributes to increasing farmers' income and can be a strategic solution to support the efficiency of pine resin tapping by Perhutani.